2015
DOI: 10.1016/j.atg.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Patients' views on incidental findings from clinical exome sequencing

Abstract: This article characterizes the opinions of patients and family members of patients undergoing clinical genomic-based testing regarding the return of incidental findings from these tests. Over sixteen months, we conducted 55 in-depth interviews with individuals to explore their preferences regarding which types of results they would like returned to them. Responses indicate a diversity of attitudes toward the return of incidental findings and a diversity of justifications for those attitudes. The majority of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
93
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 41 publications
12
93
0
Order By: Relevance
“…41,48,50 WES/WGS providers, specifically, raised the following additional concerns: justice issues related to limited resources, 45,48,49,57 complex logistics 57,58 strains on time and funding, 45,48,57,58,59 lack of participant understanding, 48,60 qualification of HCPs to manage SF, 48 and the fact that knowledge around WES/WGS is currently limited and still developing. 47,48,57 Providers were concerned that disclosure of actionable SF would warrant treatment or surveillance that may be harmful in itself or expensive.…”
Section: Resultsmentioning
confidence: 99%
“…41,48,50 WES/WGS providers, specifically, raised the following additional concerns: justice issues related to limited resources, 45,48,49,57 complex logistics 57,58 strains on time and funding, 45,48,57,58,59 lack of participant understanding, 48,60 qualification of HCPs to manage SF, 48 and the fact that knowledge around WES/WGS is currently limited and still developing. 47,48,57 Providers were concerned that disclosure of actionable SF would warrant treatment or surveillance that may be harmful in itself or expensive.…”
Section: Resultsmentioning
confidence: 99%
“…19 Other considerations for foregoing UFs, which have also been touched on in previous research included negative emotional impact; insurance ineligibility; lack of immediate (medical) action; and doubts/denial of non-medical utility claims. 16,[20][21][22][23][24][25] In contrast, other parents did not view the child's autonomy as supporting decline of certain UFs at present, even if they thought their child would become autonomous. Instead, they favored disclosure of UFs due to considerations of non-medical utility (or for (possible) future medically actionability).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have also identified this type of reasoning. 16,[19][20][21][22][23][24][25] Our findings provide important information about what parents regard as ethically justified reasons for disclosing/withholding UFs. Below we discuss how various key findings from our study are essential for morally responsible policy development and counseling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research on this subject has suggested many individuals find 9 this information actionable in other (non-medical) ways and express that they would live their 10 lives differently if they knew they were at increased risk of developing such a condition or 11 would prepare for developing the disease (Clift et al 2015;Yushak et al 2016). Our study 12 identified 21 participants with one or two copies of the APOE e4 allele, which significantly 13 increases lifetime risk for developing Alzheimer's disease (Corder et al 1993;Bertram et al 14 2010).…”
mentioning
confidence: 88%